Marilynne Robinson’s Housekeeping: Sylvie’s Fundamental Mentorship through New Western Historicism and Ecofeminist Criticism - Zastrow, Amanda (Pivot: A Journal of Interdisciplinary Studies and Thought, 2019)
In the novel Housekeeping, Marilynne Robinson discusses main character, Sylvie’s, relationship with nature in a way that revises what many New Western historians view as the Old West’s destructive ideology toward nature. Sylvie lives in opposition to what is seen as the aggressive mannerisms of Old Western males, individuals who have attempted to conquer both women and nature through their disregard for the female histories of the Old West as well as through their degradation of the faultless Western land. An effort that brings together both of these ideas, a concept that connects the maltreatment of women as well as of nature throughout history, ecofeminist philosophies are, in turn, relevant to a discussion of Robinson’s Sylvie and her New Western principles. Both viewpoints express a historical overlap of women and nature; therefore, Sylvie’s actions, which contradict the conquering mentalities of the Old West, also align with fundamental ecofeminist principles. Her actions throughout the novel possess an understanding and admiration of nature’s character as well as a voice that disagrees with the mistreatment that it receives.